Implementasi dan Pemanfaatan Continuity of Maternal Healthcare di Indonesia (Literature Review) - Azra Fauziyah Azyanti; Woro Setia Ningtyas; Martono Tri Utomo (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The high maternal mortality rate (MMR) is still a problem that Indonesia must face today. Through the results of the 2015 Inter-Census Population Survey (Supas), the government estimates that the MMR in Indonesia reaches 305 per 100,000 live births. Maternal health services that are carried out sustainably (Continuity of Maternal Healthcare) is a concept that can be applied to reduce MMR in Indonesia. This literature review aims to describe the implementation and utilization of Continuity of Care in Indonesia. Literature searches were carried out on Google Scholar, Science Direct, and PubMed search engines with the last 5 years of publication. The results of the analysis of the 7 articles obtained relate to the description of the implementation and utilization of Continuity of Maternal Healthcare in Indonesia which is influenced by sociodemographic, cultural, and performance factors of midwives. It can be concluded that the implementation of Continuity Of Maternal Healthcare is important to do in order to achieve service quality and reduce maternal mortality and morbidity in Indonesia.